Multilevel analysis of entrepreneurial intention of engineering graduating students in Ethiopia - Mesfin Mulu Ayalew (Journal of Applied Economics, 2021)
Recently, entrepreneurship has been given serious devotion due to its importance on economic growth, job creation, sources of innovation and productivity. So, this paper aims to identify the determinants of entrepreneurial intention of engineering graduating students in Ethiopia. Stratified sampling technique was employed and data were collected via questionnaire from 921 students from the target population. The study utilized regression statistics to analyze the data. The data used for this study is hierarchally structured and hence multilevel binary logistic model was used to identify the relationship between predictor and outcome variables by taking into account both level-1 (students' characteristics) and level-2 (universities characteristics) in regression relationships. The model result founds that personal attitude, perceived educational and relational support are the significant predictors of entrepreneurial intention of students at 5% level. The policymakers should facilitate entrepreneurship trainings to change attitude of students and strength the cooperation between students and fund raisers.
Keywords: 330; cluster data; entrepreneurial intention; Multilevel analysis; regression models; students